A seismic vulnerability index method for masonry schools in the province of Yazd - Azizi, Hamed (2014)
School facilities in Iran, in particular masonry schools, have shown poor performance during past earthquakes and can be identified as the most vulnerable buildings to the earthquakes. Hence, in this paper a method to perform observational-based damage assessment for brick masonry schools located in the province of Yazd, the central region of Iran, using a comprehensive database of schools is proposed. The database was obtained from the field survey forms applied for each observed school to collect the seismic influential parameters. The results of a vulnerability index method developed in Iran are employed to use in a correlation procedure as input data, aiming at obtaining the empirical fragility curves for each school inventory. The macroseismic model and GNDT II level method are two empirical methods that are combined in this procedure. The procedure is verified using damage survey data after earthquakes occurred in Iran.